Maximizing Potential : 5W+1H Reading Comprehension Strategy for Student with Moderate Intellectual Disability - Azmi, Hanita Nur; Primana, Linda (Universitas Pendidikan Mandalika, 2024)
This study aims to enhance the reading comprehension skills of elementary school students with moderate intellectual disabilities through a single-subject method. In this study, the researchers use the 5W + 1H strategy to help students understand the meaning of the text. The research data was collected using observation guidelines, which then will be analyzed by using pretest-posttest techniques to assess the subject’s reading comprehension skills improvements. Teaching the 5W + 1H principle - which emphasized the question words why and how using visual images and keywords - was found to be effective in enhancing the subject’s reading comprehension. This finding also explained that this method could maximize the potential of students with moderate intellectual disabilities. The instruction on the question words why and how was particularly effective in increasing the subject's understanding of questions as well as leading him to provide correct and contextually appropriate responses. However, using visual images as a learning aid, especially for why and how questions, seemed less effective, as evidenced by the subject's reliance on keywords within the sentence. In the future, this strategy can be employed by educators to enhance reading comprehension skills for students with moderate intellectual disabilities.